A Review of the Verse “and Do Not Cast Yourselves with Your Own Hands into Destruction” with an Approach to the Cohesion and Independence of the Verses - Mohammad Bahrami (پژوهش‌های تفسیر تطبیقی, 2021)
Received: 2020/7/12  |   Accepted: 2021/1/27AbstractMany commentators have considered the phrase “and do not cast yourselves with your own hands into destruction” (al-Baqarah: 195) related to its contiguous verses and do not believe in its generality so they have presented different perceptions about it. Different commentators regard this verse as either a prohibition on Infāq, or a prohibition on extravagance in Infāq, or a prohibition on stopping Infāq, or a prohibition on Infāq during Jihād, or a prohibition on Jihād itself and so on. Due to the subjectivity of making a relation between each of the levels, incompatibility with the revelation of the verse, and inappropriate perceptions of the narrations, the aforementioned interpretations are seriously taken into reconsideration because regarding the independence of the different sections of Surah al-Baqrah, the general perceptions of Ahl al-Bayt and jurisprudence writers about the verse as well as confusion in the spread of relationship, this verse is independent from its contiguous verses.  This research was conducted by library study along with the assessment of different theories on the exegesis of the verse and it aims to criticize the perceptions relying on the relationship between this verse and its contiguous verses in order to prove its independence.